Respuesta :

Answer:

  f(f(n)) = -n^4 -8n^2 -20

Step-by-step explanation:

As with any function evaluation, you substitute the argument for the variable and simplify.

  [tex]f(f(n))=f(-n^2-4)=-(-n^2-4)^2-4\\\\=-(n^4+8n^2+16)-4\\\\\boxed{f(f(n))=-n^4-8n^2-20}[/tex]

  • f(n)=-n^2-4

[tex]\\ \rm\hookrightarrow f(f(n))[/tex]

  • Put f(n)

[tex]\\ \rm\hookrightarrow f(-n^2-4)[/tex]

[tex]\\ \rm\hookrightarrow -(-n^2-4)^2-4[/tex]

[tex]\\ \rm\hookrightarrow -(n^4+8n^2+16)-4[/tex]

[tex]\\ \rm\hookrightarrow -n^4-8n^2-16-4[/tex]

[tex]\\ \rm\hookrightarrow -n^4-8n^2-20[/tex]